The Gorongosa elephants through war and recovery - Joyce Poole; Petter Granli (Pachyderm)
How does an elephant population recover after being pushed to the brink of extinction? In this and a separate paper on behaviour we present an account of war-induced collapse and post-war recovery of an elephant population. Mozambique’s 15-year civil war from 1977–1992 had a profound impact on the elephants of Gorongosa National Park. Elephant numbers plummeted from ~2,200 pre-war to <200 post-war impacting the structure of the population and its families, the physical appearance of the elephants, their genetic make-up and behaviour (companion study). Using individual registration, this study aimed to collect baseline data to estimate the population size, reproductive parameters and growth and to document its composition, including age and sex structure, tusk configuration, family and clan membership. A quarter of a century after the war, rapid reproductive rate and growth in numbers are indications of recovery, but the skewed sex ratio among older age classes and the prevalence of tusklessness in post-war generations are evidence of long-lasting scars.